2001
DOI: 10.1007/s00134-001-1111-7
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawing and withholding life support in the intensive care unit: a Spanish prospective multi-centre observational study

Abstract: The withholding and withdrawing of treatment was frequent in critically ill patients and was initiated primarily by physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
67
2
17

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(95 citation statements)
references
References 0 publications
9
67
2
17
Order By: Relevance
“…participants had negative attitudes towards many key items of DNR orders. In contrast, several studies [11][12][13][14]34] reported that health care providers considered that treatments are unnecessary when there is no hope of recovery. Participants' preference to general use of LSTs may be related to their religious beliefs.…”
Section: Discussionmentioning
confidence: 99%
“…participants had negative attitudes towards many key items of DNR orders. In contrast, several studies [11][12][13][14]34] reported that health care providers considered that treatments are unnecessary when there is no hope of recovery. Participants' preference to general use of LSTs may be related to their religious beliefs.…”
Section: Discussionmentioning
confidence: 99%
“…Low frequencies of LWs have also been documented in patients admitted to adult ICUs (0% to 13%) [18][19][20] and in units for the chronically critically ill (16%-38%). 21,22 These low LW rates are not unexpected, especially in the United States, given the paucity of advance care planning in America, 1 whether among the healthy, the elderly, the hospitalized, 23 those undergoing major surgical procedures, 24 or those with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Esse fato tem levado a necessidade de os médicos intensivistas restringirem a terapêutica dos seus enfermos vítimas de doença terminal. Atualmente, a maioria dos óbitos ocorridos em UTIs é precedida pela RST [15][16][17][18][19][20] . Inúmeros trabalhos [17][18][19][20] o melhor reconhecimento de que uma terapêutica possa ser fútil são os principais fatores envolvidos nessa diferença.…”
Section: Introductionunclassified